Impact of Fisheries Exports on the Participation of Fisheries in Ensuring Food Security of the Country and the Arctic Region - Anatoliy M. Vasilyev (Arctic and North, 2024)
The article examines the impact of fish products export by fishermen of the Murmansk Oblast on the realization of two main indicators prescribed in the Food Security Doctrine: the volume of products supplied to the domestic market and their economic accessibility to the population. As a result of the study, it was found that the main indicator of the Doctrine implementation — the threshold value of fish products supply to the domestic market — is not met due to its excessive export. The level of under-supply, compared to the recommendations of the Doctrine, amounted to 53.4% in 2021. Fish is supplied to the Murmansk Oblast and other regions in volumes that ensure its sale at high wholesale prices set by fishermen and with little competition. The bulk of the Arctic fish catch — up to 75%, and over 90% of cod and haddock — is exported, which is facilitated by high world prices and the low rate of the Russian ruble. Even when Russian fish is sold abroad at a discount, fish producers prefer to export it. In the absence of incentives for the supply of fishery products to the domestic market, it is advisable to increase the legal status of the Doctrine and make the implementation of its recommendations mandatory, or change the rules for allocating fishing resources to economic entities. The economic availability of cut fish for the population of the producing region — the Murmansk Oblast — is lower than the Russian average. There is a declining level of consumption. This is a consequence of the use of high prices set in the domestic market in a non-market way. There is a need to establish prices for fish products on the domestic market using auctions or exchange trading.